KAJIAN FAKTOR LINGKUNGAN PERUMAHAN PENDERITA ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS IHA KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Ulwia Ulwia (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2017)
In Maluku since 2009 Upper Respiratory Tract Infection disease was the highest disease in Maluku Health Center, with the number of cases increase until 2012. This study aims to describe the density of housing, type of floor and house ventilation with the incidence of ARI in infants. The research method is descriptive research with univariate analysis. The results showed that occupancy density, type of floor and house ventilation that did not meet the requirements showed a higher number of ARI cases compared to residential density, type of floor and house ventilation that met the requirements. It is recommended for the Puskesmas to provide more information or health education. For people who own a house with humidity, temperature, and natural lighting that is not of a good size and location, it is expected to be able to add glass tiles and repair ceilings, and open doors and windows every morning. For families with spacious but dense house occupants a spacious but dense house occupants in toddler, rooms to make use of other rooms that can be used as bedrooms. Keywords: Blood glucose levels, diet, knowledge, diet, medication, physical activity